Incorrect ventricular lead placement into the systemic right ventricle of a patient with D-transposition of the great vessels after Mustard procedure. (30th August 2016) - Powell, Adam W.; Kimball, Thomas R.
Abstract: Incorrect pacemaker lead placement into the systemic ventricle is a complication that has rarely been described in patients with D-transposition status after atrial baffle palliation. We present a case of ventricular lead misplacement in the systemic right ventricle of a patient with D-transposition of the great arteries after Mustard procedure. This case demonstrates the challenges with proper imaging of lead placement in patients with atrial baffles and long-term management of a lead in the systemic ventricle.